Harnessing Motile Amoeboid Cells as Trucks for Microtransport and ‐Assembly. Issue 3 (28th November 2018) - Nagel, Oliver; Frey, Manuel; Gerhardt, Matthias; Beta, Carsten
Abstract: Cell‐driven microtransport is one of the most prominent applications in the emerging field of biohybrid systems. While bacterial cells have been successfully employed to drive the swimming motion of micrometer‐sized cargo particles, the transport capacities of motile adherent cells remain largely unexplored. Here, it is demonstrated that motile amoeboid cells can act as efficient and versatile trucks to transport microcargo. When incubated together with microparticles, cells of the social amoeba Dictyostelium discoideum readily pick up and move the cargo particles. Relying on the unspecific adhesive properties of the amoeba, a wide range of different cargo materials can be used. The cell‐driven transport can be directionally guided based on the chemotactic responses of amoeba to chemoattractant gradients. On the one hand, the cargo can be assembled into clusters in a self‐organized fashion, relying on the developmentally induced chemotactic aggregation of cells. On the other hand, chemoattractant gradients can be externally imposed to guide the cellular microtrucks to a desired location. Finally, larger cargo particles of different shapes that exceed the size of a single cell by more than an order of magnitude, can also be transported by the collective effort of large numbers of motile cells. Abstract : Motile amoeboid cells can act as efficient and versatile trucks to transport microcargo. Cells of the social amoeba Dictyostelium discoideum readily pick up and move cargo particles. Moreover, the cell‐driven transport can be directionally guided in chemoattractant gradients that can be externally imposed or may form in a self‐organized fashion.